2007
DOI: 10.1021/bi700082v
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and Motion of Tryptophan Interfacial Anchors in Membrane-Spanning Peptides

Abstract: The tryptophans of integral membrane proteins have been suggested to play specific roles as "interfacial anchors", based on their preference for a location near the lipid head groups. Still, the underlying mechanism behind this behavior remains unclear. NMR experiments can provide an important tool to study this interaction in an actual bilayer environment. Here solid-state deuterium nuclear magnetic resonance was used to study the tryptophans in membrane-spanning model peptides from the WALP family (acetyl-GW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 60 publications
4
64
0
Order By: Relevance
“…In addition to stabilizing the concentration of monomer in aqueous solutions, inclusion of any C-terminal aromatic residue provided a lipid/water interfacial anchor. As was seen with W, F residues are commonly present (and Y to a lesser extent) at the hydrophobic/hydrophilic interface for TM segments of membrane proteins (Braun and von Heijne, 1999;Mall et al, 2000;Demmers et al, 2001;de Planque et al, 2003;Granseth et al, 2005;van der Wel et al, 2007;Hong et al, 2007 Comparing all of the summarized data in Tables 3 and 4 and the profiles shown in Figs. 16 and 17, the sequences displaying the highest ion transport activity and the second and third most left-shifted k 1/2 values are both W containing peptide sequences, NK 4 -M2GlyR-p22 T19R, S22W and NK 4 -M2GlyR-p22 Q21W, S22R.…”
Section: Wt S22wmentioning
confidence: 54%
See 1 more Smart Citation
“…In addition to stabilizing the concentration of monomer in aqueous solutions, inclusion of any C-terminal aromatic residue provided a lipid/water interfacial anchor. As was seen with W, F residues are commonly present (and Y to a lesser extent) at the hydrophobic/hydrophilic interface for TM segments of membrane proteins (Braun and von Heijne, 1999;Mall et al, 2000;Demmers et al, 2001;de Planque et al, 2003;Granseth et al, 2005;van der Wel et al, 2007;Hong et al, 2007 Comparing all of the summarized data in Tables 3 and 4 and the profiles shown in Figs. 16 and 17, the sequences displaying the highest ion transport activity and the second and third most left-shifted k 1/2 values are both W containing peptide sequences, NK 4 -M2GlyR-p22 T19R, S22W and NK 4 -M2GlyR-p22 Q21W, S22R.…”
Section: Wt S22wmentioning
confidence: 54%
“…A propensity for tryptophans residing at the aqueous/lipid interface also had been observed and tested by others (Braun and von Heijne, 1999;Mall et al, 2000;Demmers et al, 2001;de Planque et al, 2003;Granseth et al, 2005;van der Wel et al, 2007;Hong et al, 2007). Placing a W at the Cterminus sets the registry of the TM segment that spans the bilayer.…”
Section: M2glyr Studiesmentioning
confidence: 90%
“…More recently, it was shown that Trps near the C terminus of a membrane-spanning ␣-helix display a distinctly different behavior from those near the N terminus, reflected in large differences in the allowed side chain torsion angles and ring motions, highlighting the directionality of an ␣-helix relative to the bilayer/solution interface (67).…”
Section: Discussionmentioning
confidence: 99%
“…13 Considering its predominantly hydrophobic structure, the Trp side chain is expected to have an inherent affinity for the lipid bilayer. 13 Although it has been long known that Trp locates preferentially at the membrane−water interface, the mechanism by which this binding occurs is less clear. Previous binding studies have shown that indole may be partly exposed to a polar environment in bilayers but have not specified its exact location.…”
Section: ■ Introductionmentioning
confidence: 99%